Revalidating process hazard analyses - Frank, Walter L. (CCPS concept book., 2001)
The foundation of any successful process safety program is a current set of process hazard analyses (PHAs) for each of its processes. Revalidating PHAs to keep them up to date and applicable is a must. This book is derived from the experience of many companies in the chemical and hydrocarbon processing industries, and presents demonstrated, concise, and common sense approaches for a resource-effective revalidation of PHAs. It includes flowcharts, checklists, and worksheets that provide invaluable assistance to the revalidation process.